PRESTASI BELAJAR SISWA SMA DITINJAU DARI TINGKAT KEMATANGAN EMOSINYA - Husriono, Martina Winami, dan Bimono (LPPM Universitas Proklamasi 45, 2007)
The objccrivc of this study was to examine the relationship between the emotional stability and school performance among high school students. There were 70 students participated on this research. Student’s emotional stability was demonstrated from 9 factors such as the ability to be independent, empathy, sexual maturity, able to control emotion, not impulsive on decision making, able to understand the self, aNc to face the bad situation smartly It was expected that the more established one in controlling emotion, the higher his or her school performance. This hypothesis was significant with r ■ 0.365 with p ■ .002. The determinant coefficient of this research was 13.3%. which was more likely robust.